2020
DOI: 10.3390/nu12092811
|View full text |Cite
|
Sign up to set email alerts
|

Intra-Individual Double Burden of Malnutrition among Adults in China: Evidence from the China Health and Nutrition Survey 2015

Abstract: Few studies have focused on quantifying the double burden of malnutrition (DBM) phenomenon in China. We aimed to clarify the prevalence of DBM among Chinese adults as well as to examine whether usual daily dietary micronutrient status varies by body mass index (BMI) categories. In this study, a sample of 6602 adults aged 18–59 years from the China Health and Nutrition Survey (CHNS) was analyzed. Information was obtained on dietary intake and anthropometric measurements. Dietary intakes of 11 micronutrients wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 27 publications
0
21
0
Order By: Relevance
“…Micronutrient malnutrition is a serious problem in China as 200 million Chinese continue to suffer from micronutrient deficiencies [17]. A recent study found that Chinese adults (18-59 years old) have poorer diets and their intake is much lower than the estimated average requirements for several key micronutrients [18]. Biofortified crops are rich in micronutrients and can help alleviate China's micronutrient malnutrition.…”
Section: Introductionmentioning
confidence: 99%
“…Micronutrient malnutrition is a serious problem in China as 200 million Chinese continue to suffer from micronutrient deficiencies [17]. A recent study found that Chinese adults (18-59 years old) have poorer diets and their intake is much lower than the estimated average requirements for several key micronutrients [18]. Biofortified crops are rich in micronutrients and can help alleviate China's micronutrient malnutrition.…”
Section: Introductionmentioning
confidence: 99%
“…Limited research has been conducted at the individual level. Moreover, the published literature on individual-level DBM among adults has mainly examined the co-occurrence of overweight/obesity and anemia or vitamin A deficiency [ 6 , 7 , 8 , 9 , 10 , 11 ]. Characterizing DBM using anemia and vitamin A deficiency as the only measures of micronutrient deficiency may be constrained because, in other countries, iodine deficiency is also of public health significance.…”
Section: Introductionmentioning
confidence: 99%
“…This soybean situation is different, as China is not sharply self‐sufficient in this area: China imported approximately 9.8 × 10 7 tons of soybeans, which was 7.5 times its internal production, indicating a severe deficiency in this commodity (Wu et al, 2020). Although most food or feed is basically self‐sufficient from the viewpoint of fewer imports from the international market, previous studies have shown that a large proportion of the population, especially in rural areas, experiences a deficiency of nutrients (Huang et al, 2020; Zhang et al, 2016).…”
Section: Discussionmentioning
confidence: 99%